Promises and rules: The implications of rethinking the 14‐day rule for research on human embryos. (16th August 2021) - Sawai, Tsutomu; Okui, Go; Akatsuka, Kyoko; Minakawa, Tomohiro
Abstract : Removing the 14‐day limit for research on human embryos without public deliberation could jeopardize public trust in and support of research on human development.